The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.4103/ijd.ijd_74_17
|View full text |Cite
|
Sign up to set email alerts
|

A literature revision in primary cutaneous B-cell lymphoma

Abstract: The term “Primary Cutaneous B-Cell Lymphoma” (PCBCL) comprehends a variety of lymphoproliferative disorders characterized by a clonal proliferation of B-cells primarily involving the skin. The absence of evident extra-cutaneous disease must be confirmed after six-month follow-up in order to exclude a nodal non-Hodgkin's lymphoma (NHL) with secondary cutaneous involvement, which may have a completely different clinical behavior and prognosis. In this article, we have summarized the clinico-pathological features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 100 publications
1
38
0
4
Order By: Relevance
“…Primary cutaneous FCL and DLBCL‐LT are two different B‐cell lymphoma subtypes whose etiologic factors are largely unknown and characterized by a very different clinical course (La Selva et al, ). The onset of specific types of non‐Hodgkin lymphomas (NHL) in the setting of autoimmune diseases has been widely debated (Ekström Smedby et al, ) and, regarding pemphigus, a large cross‐sectional study has shown a significant association between pemphigus and chronic leukemia, multiple myeloma, and NHL (Kridin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Primary cutaneous FCL and DLBCL‐LT are two different B‐cell lymphoma subtypes whose etiologic factors are largely unknown and characterized by a very different clinical course (La Selva et al, ). The onset of specific types of non‐Hodgkin lymphomas (NHL) in the setting of autoimmune diseases has been widely debated (Ekström Smedby et al, ) and, regarding pemphigus, a large cross‐sectional study has shown a significant association between pemphigus and chronic leukemia, multiple myeloma, and NHL (Kridin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since lymphoma is a systemic disease, treatment for multicentric and cutaneous lymphoma involves systemic chemotherapy [2,12,20]. The best response rates have been seen when using multidrug protocols incorporating doxorubicin [1,2,12]; however, in cases of cutaneous lymphoma, responses to treatment may be short lived.…”
Section: Case Reports In Veterinary Medicinementioning
confidence: 99%
“…In 1996, the term "primary cutaneous large B-cell lymphoma of the leg" was proposed, which was used to classify it as a distinctive subgroup in the EORTC classification. In the last WHO-EORTC classification, this entity was finally defined PCDLBCL, leg type to reflect the predominant but not exclusive anatomic location of the lesions (Swerdlow, et al, 2008. Selva, et al, 2017.…”
Section: Clinics and Pathologymentioning
confidence: 99%
“…BCL-2, MUM1/IRF4, and FOX-P1 are strongly expressed regardless of the location of the skin lesions. A study suggests that cell-of origin is germinal center experienced and superantigen driven selected B-cell, in a stage between germinal center B-cell and plasma cell (Swerdlow, et al , 2008. Selva, et al, 2017.…”
Section: Phenotype/cell Stem Originmentioning
confidence: 99%
See 1 more Smart Citation